A Piagetian lens on cognitive development of children and youths with congenital deafblindness: a scoping review - Tosolini, Kim E.; Damen, Saskia; Janssen, Marleen J.; Minnaert, Alexander E. M. G. (Frontiers in Education, 2025)
Children with congenital deafblindness (CDB) experience several developmental delays, but an overview of studies on the cognitive development of children and youths with CDB is lacking. In present review, Jean Piaget’s theory of cognitive development was used as a framework to gather and summarize the literature on cognitive development of children and youths with CDB. A scoping review was performed to create a comprehensive overview of studies describing Piagetian cognitive skills in children with CDB. Furthermore, the literature was investigated to get insight into the role of caregivers in the development of Piagetian cognitive skills of children with CDB. Lastly, this scoping review investigated how the Piagetian cognitive skills found in the literature are assessed. Thirteen articles were included in the analysis. Descriptions of cognitive skills were mainly found for the sensorimotor and pre-operational stages. Caregiver support was found to be essential to improve learning opportunities. Dynamic assessment and questionnaires were found to be suitable methods to assess cognition in persons with CDB. More research is needed to evaluate how Piagetian skills develop over time in children and youths with CDB.